2012
DOI: 10.1017/s1355617712000069
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Executive Functioning in Amnestic Mild Cognitive Impairment: Disproportionate Deficits in Inhibitory Control

Abstract: Amnestic mild cognitive impairment (aMCI) represents a group of individuals who are highly likely to develop Alzheimer's disease (AD). Although aMCI is typically conceptualized as involving predominantly deficits in episodic memory, recent studies have demonstrated that deficits in executive functioning may also be present, and thorough categorization of cognitive functioning in MCI may improve early diagnosis and treatment of AD. We first provide an extensive review of neuropsychology studies that examined ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 99 publications
6
70
0
3
Order By: Relevance
“…Peters et al (2014) found that one of the best predictors of the conversion from MCI to AD after 2 years was the cortical thinning in the right anterior cingulate. Johnson et al (2007) reported an more increased perfusion in pMCI patients than in sMCI patients within a 5 year follow-up period in the rostral anterior cingulate. Recently, Okello et al (2009) found that faster converters (average of 1 year, as our patients) showed a higher amyloid deposition in the anterior cingulate than slow converters.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Peters et al (2014) found that one of the best predictors of the conversion from MCI to AD after 2 years was the cortical thinning in the right anterior cingulate. Johnson et al (2007) reported an more increased perfusion in pMCI patients than in sMCI patients within a 5 year follow-up period in the rostral anterior cingulate. Recently, Okello et al (2009) found that faster converters (average of 1 year, as our patients) showed a higher amyloid deposition in the anterior cingulate than slow converters.…”
Section: Discussionmentioning
confidence: 87%
“…Jelic et al (2000) reported that the best predictor of future conversion from MCI to AD was an increased theta power and a decrease in alpha activity, whereas Huang et al (2000) evidenced that the best predictor was the shift of alpha activity toward anterior brain. found that pMCI patients exhibit higher power values in the delta, theta, and alpha 1 bands, mainly over temporal and parietal areas, and also changes in frontoparietal midline coherence values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So perhaps, not all of these domains are equally sensitive to AD [42]. Among them, inhibition and working memory appeared to be particularly sensitive and were reported to be severely impaired in MCI [43][44][45][46]. One other crucial difference between the two studies is that we differentiated nonprogressor from progressor MCI.…”
Section: Discussionmentioning
confidence: 92%